Measurement of Temperature using Advanced Computing Device - N. N. Kumbhar,; G. B. Bhagat,; K. K. Gawade,; Dr. S. K. Tilekar,; Dr. P.V. Mane-Deshmukh, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The temperature parameter plays a vital role in various fields. The human body also has some amount of temperature in a specific range. In medical treatment, temperature should be maintained in the human body according to the age group. The present research article has tried to monitor the temperature of the baby incubator for better treatment of newborn babies than the old treatment. For such a study, we deployed the PSoC62 microcontroller. The results have been displayed with the help of a UART or TFT display. The displayed data is compared to an analog thermometer and a digital voltmeter. The LM35`s output is 10 mV/°C, as shown in the digital voltmeter. The water is used for the same experiment in the lab. The temperature of water is measured during heating and cooling. The measured temperature is between 81°C to 27°C. All the measured temperatures are shown in Table 1. The result of this study is that the temperature of the analog thermometer and the kit reading are the same.
Keywords: Analog Thermometer; LM35; CY8CKIT-062-WiFi-BT PSoC Microcontroller; UART